Identity Negotiation and Pragmatic Language Use: Japanese ELF Users’ Narratives in Workplace - Yamaguchi, Atsumi (Universitas Katolik Widya Mandala Surabaya, 2024)
This study explores how Japanese L2 users in a higher education workplace in Japan experience language use and identity negotiation in the English as a lingua franca (ELF) discourse community, specifically focusing on whether/how pragmatic norms are constructed. The narrative analysis of the participants’ stories of their interactional experiences shows that the macro- as well as the mezzo-level discourses circulating around the intercultural workplace discursively made a significant impact on their pragmatic aspect of language use. The analysis also highlights the challenges faced by the participants in navigating their identities between contradictory sociocultural norms and co-constructing ad-hoc pragmatic norms. Yet, developing intercultural awareness relevant to ELF communication could lead to a breakthrough in achieving interactional robustness. The findings suggest the need for further investigations into the holistic use of ELF in intercultural workplaces in East Asia, as well as the implementation of ELF-focused pragmatic instruction in English education in Japan.